Innovation for Agribusiness (InovAgro): Household- and market-level impacts of value chain interventions - Amare, Mulubrhan; Zavale, Helder; Smart, Jenny; Ghebru, Hosaena (International Food Policy Research Institute, 2022)
Agriculture, in Mozambique, is characterized by production systems that are based predominantly on rainfed conditions and on low use of yield enhancing agricultural inputs. The Innovation for Agribusiness (InovAgro) interventions were designed to increase incomes for poor smallholder farmers in northern Mozambique. Using a market systems development (MSD) approach, the InovAgro implemented value chain interventions (VCIs) to promote the development of inclusive and sustainable market systems such that the interventions impacts were felt long beyond the project’s lifespan. This study evaluated the impact of the InovAgro VCIs on households (considering a range of outcomes related to farmers’ use of yield-enhancing agricultural inputs, access to information on agricultural input and output markets, maize productivity, women and youth empowerment, and household welfare. The study also explored InovAgro VCIs outcome indicators to evaluate market-level effects, namely: systemic (long-term), sustainability, large-scale (spillover or multiplier), and unintended (positive or negative) effects. We conducted a modified randomized controlled trial (RCT) using a spatial identification strategy to classify beneficiary and nonbeneficiary households; this was supplemented with three waves of household-level panel data (2015, 2017 and 2019). We also complemented key informant interviews (KIIs) and focus group discussions (FGDs) with local stakeholders, including market actors and local authorities, with two rounds of geospatial data (2017 and 2019). Our findings show that InovAgro VCIs had a positive and significant impact on beneficiaries’ use of yield-boosting agricultural inputs and on access to information on agricultural input and output markets. Our analysis also reveals that the InovAgro VCIs boosted maize productivity and increased the marketable surplus of maize among beneficiaries. InovAgro VCIs were seen to have unintended negative effects on access to, and control over, land by women and youth in the short term; in the longer term; however, these adverse effects were reversed and became positive and significant. Our findings also show that simultaneous exposure to all three VCIs under the complete package had a positive impact on overall household welfare. We also find evidence in support of the InovAgro VCIs having a systemic market effect and producing more sustainable long-term usage of yield-boosting agricultural practices than non-InovAgro VCIs. Our results elucidate that InovAgro VCIs benefitted large numbers of smallholder farmers beyond the project’s direct sphere of influence and targeted beneficiaries. The key takeaway message from our findings is that a more intense VCI, that is, delivery of the complete package, appears to be necessary to achieve a long-term positive effect on overall household welfare.